Some radiation properties at Mizuho Station, East Antarctica in 1980 - Ishikawa, Nobuyoshi; Kobayashi, Shun'ichi; Ohata, Tetsuo; Kawaguchi, Sadao (1982)
P(論文) Measurements of radiation components were carried out at Mizuho Station in a period from 1979 to 1981,selecting the heights 1.0 and 30m (the top of a meteorological tower), as a part of the Polar Experiment in Antarctica (POLEX-South), with the following findings on radiation properties from data obtained in 1980 : The annual mean value of net radiation was about -26ly/day (-1.1MJ/m^2・day). Concerning the amount of outgoing long-wave (terrestrial) and incoming long-wave (atmospheric) radiation, the former was expressed by the temperature near the snow surface with adequate accuracy; the latter was fairly sensitive to the cloud amount; a difference in the latter between two different heights was much greater than that in the former, especially in the austral winter. Finally the presence of a surface temperature inversion had some influences on the atmospheric radiation. departmental bulletin paper